Promoting Values of Religious Tolerance through Moroccan ELT Textbooks - Hassan Ait Bouzid (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2016)
This paper examines the religious content of three Moroccan second year Baccalaureate ELT textbooks. It studies the representation of religion as a cultural perspective in these textbooks to investigate whether they raise Moroccan learners’ awareness of other religions. It is built on the premise that the spread of religious intolerance is fueled by being insufficiently or inappropriately informed about local and foreign religions. It therefore draws the attention of ELT practitioners to recognizing the role ELT textbooks could play in reducing illiteracy about religions and fostering positive attitudes towards other religions. The study evolved within the theoretical framework of the Standards-Based Approach. It adopted a concurrent triangulation design and used mixed content analysis to analyze the data. The findings revealed that the examined textbooks do not sensitize learners about respect for diversity, tolerance and peaceful coexistence among different religions. Ultimately, some ways in which religious antagonism could be minimized are suggested.